Does liver cirrhosis lead to inferior outcomes following cardiac surgery?. (20th July 2018) - Wallwork, Kate; Ali, Jason M; Abu-Omar, Yasir; De Silva, Ravi
Summary: A best evidence topic in cardiac surgery was written according to a structured protocol. The question addressed was: Do patients with liver cirrhosis undergoing cardiac surgery have inferior clinical outcomes? Altogether, 1627 papers were found using the reported search, of which 8 represented the best evidence to answer the clinical question. The authors, journal, date and country of publication, patient group studied, study type, relevant outcomes and results of these papers are tabulated. We conclude that these studies demonstrate that cirrhotic patients have significantly poorer clinical outcomes following cardiac surgery than would be predicted by conventional risk scoring systems. This includes both in-hospital mortality and rates of major complications (bleeding, cardiac, infective, renal and respiratory), which would likely lead to an increased hospital length of stay and, therefore, an associated cost. Evidence supports that the Model for End-stage Liver Disease and Child–Turcotte–Pugh cirrhosis severity scoring systems can be used to stratify risk in cirrhotic patients undergoing cardiac surgery and should be considered for inclusion in future cardiac surgery risk scoring systems.